1999
DOI: 10.1002/(sici)1097-0215(19990702)82:1<137::aid-ijc23>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Tight junction protein zo-2 is differentially expressed in normal pancreatic ducts compared to human pancreatic adenocarcinoma

Abstract: Differential display of hamster mRNA identified a fragment present in normal pancreatic duct cells that is not expressed in pancreatic duct carcinoma cells. Sequence analysis showed an 88% and 82% identity, respectively, to the cDNA of the canine and human tight junction zo‐2 gene. Semi‐quantitative RT‐PCR analysis of human ZO‐2 revealed a striking difference in the expression of various regions of the ZO‐2 transcript in normal and neoplastic cells and the presence of an abnormality at the 5′‐end of mRNA. RACE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 31 publications
(37 reference statements)
2
25
0
Order By: Relevance
“…The literature regarding the two described ZO-2 isoforms is extremely scarce and reports that the expression of specific ZO-2 isoforms is dependent on the cell type suggest different biological functions for these two molecules [7]. In agreement with our observations, Chlenski et al [6] have not detected isoform A in pancreatic adenocarcinoma when compared to normal tissues, while isoform C was detected in all tumor samples. Thus, our results suggest that a diminution of the ZO-2A form could be specifically involved in the process of tumor progression of bronchopulmonary carcinomas.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The literature regarding the two described ZO-2 isoforms is extremely scarce and reports that the expression of specific ZO-2 isoforms is dependent on the cell type suggest different biological functions for these two molecules [7]. In agreement with our observations, Chlenski et al [6] have not detected isoform A in pancreatic adenocarcinoma when compared to normal tissues, while isoform C was detected in all tumor samples. Thus, our results suggest that a diminution of the ZO-2A form could be specifically involved in the process of tumor progression of bronchopulmonary carcinomas.…”
Section: Discussionsupporting
confidence: 92%
“…ZO-2C protein is 23 amino acids shorter at the N-terminus than ZO-2A [6,7]. Three others forms have also been described, two derived from form A and one from form C. However little is known about the potential functional differences between these isoforms.…”
Section: Introductionmentioning
confidence: 99%
“…Certain studies have suggested that some of the cell adhesion and cytoskeletal proteins could subserve an additional and important function, namely the suppression of the malignant phenotype of cells in tumourigenesis (39). Whilst the barrier and fence functions of TJs have been well appreciated in the past, it was not till later that the concept of the TJ as a complex, multiprotein structure with roles in other cellular processes such as cell polarity, proliferation and differentiation, was recognised (40).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the expression levels of ZO-1 and ZO-2 are dysregulated in different types of cancers and, in the case of breast cancer, low expression of ZO-1 has been correlated with a poor prognosis (Chlenski et al, 2000;Chlenski et al, 1999;Hoover et al, 1998;Kleeff et al, 2001;Martin et al, 2004;Morita et al, 2004;Resnick et al, 2005;Takai et al, 2005). Similarly, several junctional scaffolding proteins are bound and inactivated by viral oncogenes (Glaunsinger et al, 2001;Latorre et al, 2005).…”
Section: Tjs In Diseasementioning
confidence: 99%